Intoxication as a defence under the Malaysian panel code / Rodali Seman - Seman, Rodali (Faculty of Law, 1983)
The law of intoxication as a defence for a criminal charge is dealt with by section 85 and 86 of the Malayan Penal Code. Only intoxication caused by alcohol or drugs is recognised as a defence for a criminal charge. Intoxication caused by alcohol is often known as drunkenness. The English law dictionary by Earl Jowit, published by Sweet and Maxwell Limited, 1959, defined drunkenness as intoxication with strong liquor, habitual inebriety. There are so many kind of alcohol am drugs which existed today. Sane examples ef drugs are opium, Indian hemp, morphine, heroin, cocaine, ugonine, and L.S.D. Some example of alcohol are Carlsberg, Remy Martin, C.O. Cognac, bramy, Special Brew and Guinness stout